Associations between vision impairment and driving performance and the effectiveness of vision-related interventions: A systematic review. (January 2023) - Nguyen, Helen; Luca Di Tanna, Gian; Coxon, Kristy; Brown, Julie; Ren, Kerrie; Ramke, Jacqueline; Burton, Matthew J.; Gordon, Iris; Zhang, Justine H.; Furtado, João M.; Mdala, Shaffi; Fiston Kitema, Gatera; et al.
Highlights: An up-to-date systematic review looking at vision and driving performance. Poor vision negatively impacts a variety of driving performance measures. Cataract surgery and corrective lenses can reduce driving errors. Current literature is highly heterogeneous; no consensus on performance measures. There needs to be more high quality studies from low-middle income countries. Abstract: Introduction: This systematic review aims to (1) investigate the associations between vision impairment and driving performance, and (2) evaluate the effectiveness of vision-related interventions to improve driving performance. Method: Medline (Ovid), EMBASE and Global Health electronic databases were searched from their inception to March 2022 for observational and interventional English-language studies. The population of focus were licensed drivers of all ages of four-wheeled motorised vehicles. The primary outcome was measures of driving performance from naturalistic driving and/or on-road closed circuits. All screening, data extraction and critical appraisals were completed independently by two authors. Results: 27 studies (n = 6358 participants) from the 4281 identified in the search were included in this review. All but one study, an RCT, were observational. Only 2 cross-sectional studies were rated as high risk of bias. The majority of papers (80 %) were limited to older drivers. There were 33 different performance measures reported. Poor driving performance was associated with glaucoma, AMD and monocularity, and measures of vision function including contrast sensitivity, visual acuity and visual fields. From the vision-related interventions identified only cataract surgery and toric refractive correction for astigmatism were shown to improve driving performance on selected measures. Conclusion: Despite differences in outcome measures, there is consistent evidence for associations between vision impairments and poor driving performance. This review highlights the importance vision has on an individual's ability to safely drive and complete common manoeuvres. Early detection and management of eye conditions may help decrease the likelihood of crashing and road traffic injuries.